Integrating Yusuf Al-Qaradawi’s Concept of Maqasid Zakat with the Maqasid al-Muʿāmalāt al-Māliyyah for the Development of Islamic Economics - Hambari; Qurroh Ayuniyyah; Hilman Hakiem; Fithriyyah Shalihati; Mohammad Hidir Baharudin (LAN TABUR: Jurnal Ekonomi Syariah The Islamic University of KH. Achmad Muzakki Syah Jember, East Java. Jember Jln. Manggar Gebang Poreng 139A Patrang Jember Jawa Timur, 2026)
This study explores the integration of Yusuf al-Qaradawi’s concept of maqāṣid al-zakāt with the objectives of maqāṣid al-muʿāmalāt al-māliyyah as a unified framework for advancing Islamic economics. Al-Qaradawi emphasizes zakat not only as an act of worship but as a dynamic socio-economic tool that aims to eliminate poverty, ensure equitable wealth distribution, and promote social solidarity. Meanwhile, Islamic financial transactions rooted in maqāṣid al-sharīʿah prioritize ethical principles such as justice, wealth preservation, transparency, and risk-sharing. Through a qualitative conceptual analysis using thematic synthesis and comparative ijtihād, this research reveals that both systems share a mutual aim: achieving public welfare (maṣlaḥah). The convergence of these maqāṣid enables a comprehensive model that combines redistributive mechanisms (zakat) with productive instruments (Islamic finance). This model addresses critical challenges in Muslim societies such as poverty, underdevelopment, and inequality, while aligning Islamic economics with sustainable development goals (SDGs). The study proposes practical collaboration between zakat institutions and Islamic financial entities and highlights the significance of ethical reintegration in financial design. By adopting Al-Qaradawi’s purposive jurisprudence, this research offers a transformative framework for Islamic economic development that balances legal compliance, spiritual obligation, and social justice.